PENGARUH CITRA MEREK, GAYA HIDUP DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA PERUSAHAAN PEMBIAYAAN DI GRESIK - Susi, Susi Hardianti Sabana Putri; Aslamiyah, Suaibatul (FEB Universitas Sam Ratulangi Manado, 2024)
This study aims to determine the influence of brand image, lifestyle and service quality on purchase decisions. The research method used in this study is quantitative descriptive. Data collection uses a questionnaire with a total of 254 respondents. By using multiple linear regression analysis and data processing using SPSS. The results of the study show that brand image has a significant influence on purchase decisions. Lifestyle has a significant effect on purchasing decisions and service quality has a significant effect on purchasing decisions